P1848SUSTAINABILITY OF ACTIVE LIFESTYLE INTERVENTION BENEFITS FOR KIDNEY TRANSPLANT RECIPIENTS AFTER STUDY COMPLETION: POST-HOC ANALYSIS OF THE CAVIAR RANDOMISED CONTROLLED TRIAL. (6th June 2020) - Driscoll, Joanne; Kuningas, Kulli; Dutton, Mary; Day, Edward; Sharif, Adnan
Abstract: Background and Aims. CAVIAR (Comparing glycaemic benefits of Active Versus passive lifestyle Intervention in kidney Allograft Recipients) was a single-centre, randomised, controlled trial that recruited stable kidney transplant recipients without diabetes between 3-24 months' post-transplantation. Participants were randomly assigned to active (personalised renal dietetic-led sessions using evidence-based behaviour change techniques) versus passive lifestyle intervention (current standard of care) for a six-month intervention period. Our findings showed encouraging clinical improvements including reduction in weight (mean difference -2.47kg [-.401 to -0.92], p=0.002), fat mass (-1.537 [-2.947 to -0.127], p=0.033) and rates of post-transplantation diabetes (7.6% versus 15.6% respectively, p=0.123). However, evidence from the general population suggests lifestyle intervention behaviour change techniques must be sustained to achieve the greatest benefit. It is unclear whether the same is true for kidney transplant recipients. Therefore, the aim of this study was to conduct a post-hoc analysis of the CAVIAR study to explore 1-year study outcomes (6-months after completion of the study interventions) to explore how clinical outcomes have evolved. Methods. The methodology of the CAVIAR study has already been summarised above and main findings published ( Kuningas et al. Transplantation 2019; early online ). Assessment of 1-year study outcomes was prespecified in the CAVIAR trial protocol to understand post-intervention outcomes. Between August 2015 and December 2017, 130 individuals were recruited to the trial and final study visits were conducted in February 2018. Electronic patient records were analysed for all study participants and 1-year outcome data (up to August 2019) were extracted in relation to cardio-metabolic risk outcomes where available. The trial is registered on clinicaltrials.org (identifier: NCT02233491). Results. While CAVIAR participants randomised to active versus passive lifestyle intervention demonstrated beneficial weight change in the six-month study period with a negative mean difference, in the six-month period after study completion we observed the opposite effect with a positive mean difference (+1.23 kg [-0.05 to 2.51], p=0.060). Two participants from both active and passive intervention arms subsequently developed post-transplantation diabetes in the six-months after study closure, although difference in post-transplantation diabetes rates remained clinically significant at 1-year (10.6% versus 18.8% respectively, p=0.143). There was no significant correlation between study baseline Situational Motivation Score components (intrinsic motivation, intrinsic regulation, extrinsic regulation or amotivation) and weight change either during or after CAVIAR study completion Conclusion. Our post-hoc analysis of the CAVIAR study suggest active lifestyle intervention using renal dietitian-led behaviour change techniques must be a continuous rather than a one-off strategy to sustain long-term clinical benefits and is unrelated to baseline motivation. This has implications for service delivery and workforce planning for established kidney transplant programs across Europe.